Comprehensive assessment of local and regional aortic stiffness in patients with tricuspid or bicuspid aortic valve aortopathy using magnetic resonance imaging. (1st March 2021) - Pascaner, Ariel F.; Houriez--Gombaud-Saintonge, Sophia; Craiem, Damian; Gencer, Umit; Casciaro, Mariano E.; Charpentier, Etienne; Bouaou, Kevin; Cesare, Alain De; Dietenbeck, Thomas; Chenoune, Yasmina; Kachenoura, Nadjia; Mousseaux, Elie; et al.
Abstract: Background: We aimed to provide a comprehensive aortic stiffness description using magnetic resonance imaging (MRI) in patients with ascending thoracic aorta aneurysm and tricuspid (TAV-ATAA) or bicuspid (BAV) aortic valve. Methods: This case-control study included 18 TAV-ATAA and 19 BAV patients, with no aortic valve stenosis/severe regurgitation, who were 1:1 age-, gender- and central blood pressures (BP)-matched to healthy volunteers. Each underwent simultaneous aortic MRI and BP measurements. 3D anatomical MRI provided aortic diameters. Stiffness indices included: regional ascending (AA) and descending (DA) aorta pulse wave velocity (PWV) from 4D flow MRI; local AA and DA strain, distensibility and theoretical Bramwell-Hill (BH) model-based PWV, as well as regional arch PWV from 2D flow MRI. Results: Patient groups had significantly higher maximal AA diameter (median[interquartile range], TAV-ATAA: 47.5[42.0–51.3]mm, BAV: 45.0[41.0–47.0]mm) than their respective controls (29.1[26.8–31.8] and 28.1[26.0–32.0]mm, p  < 0.0001), while BP were similar ( p  ≥ 0.25). Stiffness indices were significantly associated with age (ρ ≥ 0.33), mean BP (arch PWV: ρ = 0.25, p  = 0.05; DA distensibility: ρ = −0.30, p  = 0.02) or AA diameter (arch PWV: ρ = 0.28, p  = 0.03; DA PWV: ρ = 0.32, p  = 0.009). None of them, however, was significantly different between TAV-ATAA or BAV patients and their matched controls. Finally, while direct PWV measures were significantly correlated to BH-PWV estimates in controls (ρ ≥ 0.40), associations were non-significant in TAV-ATAA and BAV groups ( p  ≥ 0.18). Conclusions: The overlap of MRI-derived aortic stiffness indices between patients with TAV or BAV aortopathy and matched controls highlights another heterogeneous feature of aortopathy, and suggests the urgent need for more sensitive indices which might help better discriminate such diseases. Highlights: Ascending aorta aneurysm with tricuspid or bicuspid aortic valve. 1:1 age-, gender- and blood pressure-matching with healthy volunteers. Noninvasive, quantitative, comprehensive MRI description of aortic stiffness. Central instead of peripheral brachial blood pressures. Simultaneous blood pressure and MRI acquisition.